2009
DOI: 10.1093/database/bap022
|View full text |Cite
|
Sign up to set email alerts
|

Cildb: a knowledgebase for centrosomes and cilia

Abstract: Ciliopathies, pleiotropic diseases provoked by defects in the structure or function of cilia or flagella, reflect the multiple roles of cilia during development, in stem cells, in somatic organs and germ cells. High throughput studies have revealed several hundred proteins that are involved in the composition, function or biogenesis of cilia. The corresponding genes are potential candidates for orphan ciliopathies. To study ciliary genes, model organisms are used in which particular questions on motility, sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
134
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 45 publications
1
134
0
2
Order By: Relevance
“…We discuss only DYDC2 because of the similarity. As expected for an RSP2 orthologue, DYDC2 was found in the human cilium proteome and is listed in the cilium proteome database (2,42). Inferred from expressed sequence tags (EST), it is enriched in the lung and the testis, which contain cells with motile cilia or flagella (Hs.512782 in the UniGene database [http://www.ncbi.nlm.nih.gov/]).…”
Section: Resultsmentioning
confidence: 55%
“…We discuss only DYDC2 because of the similarity. As expected for an RSP2 orthologue, DYDC2 was found in the human cilium proteome and is listed in the cilium proteome database (2,42). Inferred from expressed sequence tags (EST), it is enriched in the lung and the testis, which contain cells with motile cilia or flagella (Hs.512782 in the UniGene database [http://www.ncbi.nlm.nih.gov/]).…”
Section: Resultsmentioning
confidence: 55%
“…At first, ubiquitinated proteins have been reported to be present in cilia and flagella 52 , and the K63-specific E2 ubiquitinconjugating enzyme Ubc13 is present in the ciliome of various species [52][53][54][55] . Next, protein ubiquitination was involved in flagellar disassembly 52 .…”
Section: Discussionmentioning
confidence: 99%
“…A key step in understanding ciliary biology, and thus the etiology of ciliopathies, is to identify the various components that participate in the generation and function of these organelles. Over the years, a variety of strategies have been used to determine the genes and proteins required in different kinds of cilia (Arnaiz et al, 2009;Gherman et al, 2006;Inglis et al, 2006). These screens have revealed that cilia are complex organelles, with hundreds (if not thousands) of components involved in their assembly, structure and function, the expression of which must be precisely coordinated during cilia formation.…”
mentioning
confidence: 99%